TALK AND CHILL CARDS FOR IMPROVING EFL SPEAKING SKILL - Dede Rosyadi ZA (JETA (Journal of English Teaching and Applied Linguistic), 2023)
In this era.There are many different types of media that are widely used in English language learning. One is the Talk and Chill card. This media can help Students' in improving their speaking skills.The aim of this research paper is to know whether the students' speaking skills have improved significantly. Communication skills using flashcards. Class X, with a total of 24 students, was selected as a sample for this study. This pre-test study uses a pre-test and a post-test. These exams take the form of oral exams. Data from these tests are calculated using statistical models. Studies have shown that students' speaking skills improve significantly after receiving treatment. Therefore, talk and chill cards can be used as a different medium to teach English, especially speaking skills, in EFL classrooms.